A survey of contemporary economics - Ellis, Howard Sylvester; American Economic Association (Illinois Richard D. Irwin, 1948)
The primary purpose of the present volume is to provid to the economist outside a particular field in intelligible and reliable account of its main ideas both analytical devices and their practical application to public policy which have evolved during the last ten or fifteen years.
Includes index
Includes bibliographical references
aia 15/01/2019
Loans
Keywords: Economics; Economic theory